Science for the people: the climate justice approach. President Mary Robinson - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Introduction: Lindiwe Sibanda. Speaker: Mary Robinson, President, The Mary Robinson Foundation for Climate Justice (MRFCJ), former President of Ireland and United Nations High Commissioner for Human Rights: Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday